Analysis of the Impact of Mileage, Service Costs, and Availability of Medical Personnel on Patient Satisfaction in Accessing Health Services in Disadvantaged Areas in Indonesia - Yana Priyana; Wahidin Wahidin; Heri Setiyawan (Westscience Press, 2024)
This study examines the impact of distance travelled, cost of service, and availability of medical staff on patient satisfaction in accessing healthcare services in disadvantaged areas of Indonesia. Using a quantitative approach, data were collected from 50 respondents through a structured questionnaire, employing a Likert scale of 1-5. Multiple regression analysis was performed using SPSS version 26 to determine the relationships between the independent variables (distance travelled, cost of service, and availability of medical staff) and the dependent variable (patient satisfaction). The results indicate that distance travelled and cost of service have significant negative impacts on patient satisfaction, while the availability of medical staff positively influences satisfaction. These findings provide valuable insights for policymakers and healthcare providers in addressing the barriers to healthcare access in underserved regions of Indonesia and improving patient satisfaction.